2002
DOI: 10.1103/physrevc.65.054322
|View full text |Cite
|
Sign up to set email alerts
|

Gamow-Teller strength and the spin-isospin coupling constants of the Skyrme energy functional

Abstract: We investigate the effects of the spin-isospin channel of the Skyrme energy functional on predictions for Gamow-Teller distributions and superdeformed rotational bands. We use the generalized Skyrme interaction SkO' to describe even-even ground states and then analyze the effects of time-odd spinisospin couplings, first term by term and then together via linear regression. Some terms affect the strength and energy of the Gamow-Teller resonance in finite nuclei without altering the Landau parameter g ′ 0 that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
290
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(311 citation statements)
references
References 94 publications
19
290
2
Order By: Relevance
“…This confirms and extends a conclusion of Bender et al [40]. These authors have shown in a similar manner and for another Skyrme parametrization SkO' that the dynamical moment of inertia J (2) of the SD band of 152 Dy depends mainly on the spin-isospin Landau parameter g ′ 0 and not so much on the actual values of the individual coupling constants C s 1 and C T 1 .…”
Section: T22 T26 T44 T62supporting
confidence: 90%
See 2 more Smart Citations
“…This confirms and extends a conclusion of Bender et al [40]. These authors have shown in a similar manner and for another Skyrme parametrization SkO' that the dynamical moment of inertia J (2) of the SD band of 152 Dy depends mainly on the spin-isospin Landau parameter g ′ 0 and not so much on the actual values of the individual coupling constants C s 1 and C T 1 .…”
Section: T22 T26 T44 T62supporting
confidence: 90%
“…This choice is not unique. Other groups use SLy4 in their cranked HFB or QRPA calculations by setting just C T t = 0, keeping C s t and C ∆s t at their Skyrme-force values [21,28,40].…”
Section: F Parameterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilsson levels in the vicinity of the Fermi surface for nearly spherical nuclei, there appears another type of ambiguity in choosing the Slater determinants representing the anti-aligned configurations. Within the set of nuclei studied in this work, this ambiguity manifests itself particularly strongly in 42 Sc, where we deal with four possible anti-aligned MF configurations built on the Nilsson orbits originating from 0.5 the spherical νf 7/2 and πf 7/2 sub-shells. These configurations can be labeled in terms of the quantum number K as |νK ⊗ πK with K = 1/2, 3/2, 5/2, and 7/2.…”
Section: B Nearly Degenerate K-orbitalsmentioning
confidence: 99%
“…This is an intriguing result, which indicates that an increase of the bulk symmetry energy -that tends to restore the isospin symmetry -is partly compensated by other effects. The most likely origin of this compensation mechanism is due to the time-odd spin-isospin mean fields, which are poorly constrained by the standard fitting protocols of Skyrme EDFs [41][42][43]. For instance, if one compares the Landau-Migdal parameters characterizing the spin-isospin time-odd channels [41][42][43] To illustrate the compensation mechanism related to the bulk symmetry energy and g 0 , in Fig.…”
Section: Theoretical Uncertainties and Error Analysismentioning
confidence: 99%